AS1411 aptamer conjugated gold nanoclusters as a targeted radiosensitizer for megavoltage radiation therapy of 4T1 breast cancer cells. Issue 8 (23rd January 2018) - Ghahremani, Fatemeh; Shahbazi-Gahrouei, Daryoush; Kefayat, Amirhosein; Motaghi, Hasan; Mehrgardi, Masoud A.; Javanmard, Shaghayegh Haghjooy
Abstract : In the present study, AS1411 aptamer conjugated gold nanoclusters (GNCs) have been introduced as a targeted radiosensitizer for enhancing megavoltage radiation therapy efficacy. Abstract : In the present study, AS1411 aptamer conjugated gold nanoclusters (GNCs) have been introduced as a targeted radiosensitizer for enhancing megavoltage radiation therapy efficacy. GNCs with an ultra-small gold core and a bovine serum albumin shell (BSA) as a versatile nano-platform were synthesized and conjugated to AS1411 aptamer (Apt–GNCs). Due to nucleolin overexpression in breast cancer cells and high affinity of the AS1411 aptamer to nucleolin, mouse mammary carcinoma cell line (4T1) was selected as the malignant cells and murine fibroblast (L929) was used as a normal cell line. Flow cytometry assessments reveal a significant increase in GNCs uptake by the cancer cells in the presence of the aptamer as the targeting agent. Inductively coupled plasma optical emission spectrometry (ICP-OES) measurements demonstrate 4 times more Apt–GNCs uptake by 4T1 cells than the normal cells at a concentration ratio of 1 : 40 (4 μM aptamer and 160 μM GNCs at 24 h incubation). Moreover, the combination of megavoltage radiation therapy and Apt–GNCs as radiosensitizer causes effective cancer cell death and a dose enhancement factor (DEF) of about 2.7 in clonogenic survival assay is obtained.